2014
DOI: 10.1007/s10695-014-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid levels impact lipoprotein lipase, hormone-sensitive lipase, and fatty acid synthetase gene expression in three tissues of adult GIFT strain of Nile tilapia, Oreochromis niloticus

Abstract: The objective of this study was to assess the effects of dietary lipids on growth performance, body composition, serum parameters, and expression of genes involved in lipid metabolism in adult genetically improved farmed tilapia (GIFT strain) of Nile tilapia, Oreochromis niloticus. We randomly assigned adult male Nile tilapia (average initial body weight = 220.00 ± 9.54 g) into six groups consisting of four replicates (20 fish per replicate). Fish in each group were hand-fed a semi-purified diets containing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 71 publications
10
33
2
Order By: Relevance
“…In the present study, the optimal dietary lipid level for larval GIFT tilapia was 8.56%, according to the secondary curve equation, which is similar to the dietary lipid level requirement of adult GIFT tilapia(7.66–8.79% lipid levels) (Tian et al . ). However, this optimal dietary lipid level for larvae is lower than that for juvenile hybrid tilapia and GIFT tilapia (12% and 9.34% respectively) (Chou & Shiau ; Wang et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, the optimal dietary lipid level for larval GIFT tilapia was 8.56%, according to the secondary curve equation, which is similar to the dietary lipid level requirement of adult GIFT tilapia(7.66–8.79% lipid levels) (Tian et al . ). However, this optimal dietary lipid level for larvae is lower than that for juvenile hybrid tilapia and GIFT tilapia (12% and 9.34% respectively) (Chou & Shiau ; Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Mjoun, Rosentrater and Brown () recommended that dietary fat levels should be 8–12% for tilapia weighing up to 25 g and 6–8% for larger fish. Tian, Wu, Yang, Jiang, Liu and Wen () revealed that the optimal dietary lipid level for maximum growth performance of adult Genetically Improved Farmed Tilapia (GIFT) tilapia is 7.66–8.79% and that increasing dietary lipid level contributed to increase tissue and whole‐body lipid levels. Increased culture of GIFT Nile tilapia in China is based on their rapid growth rate, high fillet yield and good disease resistance (Qiang, Yang, Wang, Kpundeh & Xu ).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenteric adipose tissue is recognized as an important fat storage tissue (Weil et al, ) and substantially expresses lipid metabolic enzymes in fish (Tian, Lu, et al, ; Tian, Wu, et al, ). In this study, the mRNA levels of fas decreased after AICAR treatment, while the mRNA levels of srebp‐1 , hsl and lpl remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used for these genes are shown in Table . All primers were synthesized by BGI and have been used successfully in grass carp in previous studies (Cheng et al, , ; Hu et al, ; Leng et al, ; Sun et al, ; Tian, Lu, et al, ; Tian, Wu, et al, ). The key glucose metabolic enzymes in the liver, muscle and heart were tested (Hemre et al, ; Hu et al, ), and the lipid metabolic factors in the liver, muscle and adipose tissue were detected, respectively (Weil et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In dietinduced obese mice, transgenic overexpression adropin exhibit inhibition LPL genes expression in adipose tissue (Kumar et al 2008). Given that the hepatic LPL gene is substantially expressed in fish (Albalat et al 2006, Feng et al 2014, Tian et al 2015, correlations between adropin and LPL were suspected to play a role in lipid metabolism at the tilapia hepatocytes level. This idea is supported by our in vitro studies with tilapia hepatocytes in which adropin was effective in elevating LPL release, cellular LPL content and total LPL production.…”
Section: Discussionmentioning
confidence: 99%